Hoe de Nederlandse juffers met liefde omgingen: De wereld van de gevoelens in Historie van mejuffrouw Sara Burgerhart (1782) van Elisabeth Wolff en Agatha Deken - Urbaniak, Jan (Acta Neerlandica, 2023)
Love played an important role in Wolff and Deken’s 18th-century bestseller, The History of Miss Sara Burgerhart. The attitude to the feelings allowed the reader to get to know the novel’s characters thoroughly. That how they talked about love and made love helped in the reconstruction of their character drawing. Sara – the title character of the novel – went through a development that also changed her conception of love: from the irresponsible teenager who enjoyed the company of various, sometimes rowdy boys, she gradually became an ideal wife and mother, with whom the sincere love prevailed. In this contribution, several models of love in the Sara Burgerhart epistolary novel were contrasted: the French-tinted, sentimentally colored libertine love game with the calm, reasoned feelings in the Dutch way. The result of such contradiction is easy to guess.